The Existence of Video Debate Final Pilkada DKI 2017 on The Youtube - Rachmaniar (Fakultas Ilmu Komunikasi Universitas Pancasila, 2017)
The purpose of this research is to know the existence of video Debat Final Pilkada DKI 2017 on the channel YouTube, viewed from TV station which uploading video Debat Final Pilkada DKI 2017 in the channel YouTube, and netizen comment related to video Debat Final Pilkada DKI 2017 in the channel YouTube. The method used in this research is qualitative method with virtual ethnography approach to know the existence of video Debat Final Pilkada DKI 2017 in the channel YouTube. The main object of this research is video Debat Final Pilkada DKI 2017 in the channel YouTube. Data collection techniques are conducted through participatory observation and literature studies. The results of this study indicate that some television stations uploaded video Debat Final Pilkada DKI 2017 in the channel YouTube. The television stations are CNN, Kompas TV, and Metro TV. Then netizen comments related to the contents of the video Debat Final Pilkada DKI 2017 in the channel YouTube are: 1) netizens often insult the candidate pairs that are not his choice, 2) netizens mutually insulting other netizens who support one of the candidate pairs, 3) netizens boast of candidate pairs of their choices, 4) netizens describe program the candidate pair of their choices, 5) netizens questioned the candidate pair program that is not their choice, and 6) netizens argue with other netizens who have different options with them.